UV-PHOTOMETRY WITH THE 1.2 M SCHMIDT TELESCOPE IN BALDONE - Eglitis, I.; Eglite, M.; Pakuliak, L. K.; Andruk, V. M. (Одеські астрономічні публікації, 2016)
TheUniversityofLatvia's Institute of astronomy possesses a collection of 22 thousand photographic plates taken by the1.2 mSchmidt telescope located at the Baldone observatory. Among others, there are 767 astronegatives in this collection obtained in 314 sky areas using the Johnson U-filter. The field of view of each negative covers 19 square degrees. The plate scale is 72”/mm. The digitizing of the UV-collection has started in June 2016 with EPSON EXPRESSION 10000XL flatbed scanner. The general aim of the digitizing is to obtain UV-magnitudes and positions of all objects registered on the plates. Up to date near a half of the UV-collection is digitized. 24 digitized MEGA program plates of the collection were used for the preliminary investigation of the quality of photographic material and scanner systematic behavior. The catalog of positions and UV-magnitudes of 68.784 stars and galaxies for 12 regions allows evaluating the expected accuracy of the whole observed material. The estimated accuracy for all objects is σαδ = ±0.28" and σU = ±0.20m for positions and brightness respectively. For the stars with U = 8m – 14m these errors are σαδ = ±0.11" and σU = ±0.09m. The convergence of coordinates with respect to the coordinates of the reference system Tycho2 is σαδ= ±0.06". The conformity with photoelectric Upe-magnitudes is ±0.13m.